The Peningkatan Pengetahuan Tentang Persiapan Pranikah Sebagai Upaya Kehamilan Sehat Untuk Mencegah Stunting - Nora Rahmanindar; Nilatul Izah; Puji Tri Astuti; Seventina Nurul Hidayah; Evi Zulfiana (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Child marriage is one of the factors that boost the high stunting rate in Indonesia, as many as 30-35 percent of stunting cases in children are born to women who marry at a young age, there must be education about good reproductive health and preparing for a healthy pregnancy. This approach needs to be done early, including psychological and economic preparation. Therefore, pre-marital preparation, providing pre-marital counseling to prevent stunting, provide an understanding of reproductive health. The government is currently trying to achieve the target of reducing stunting prevalence in accordance with the target in the 2020-2024 RPJMN by 14% by the end of 2024. The National Strategy for the Acceleration of Stunting Prevention (Stranas Stunting) has established adolescents as one of the important targets in efforts to accelerate stunting prevention. Therefore, intervention in the adolescent age group, especially adolescent girls, is one of the main interventions that must be carried out in preventing stunting. Actions that need to be taken in overcoming the high prevalence of stunting are prevention. Prevention of stunting is carried out through nutritional and non-nutritional approaches, the targets of the importance of improving nutrition and health are adolescents, prospective brides, and pregnant women. So far, many people do not understand the importance of conditions before the conception process (preconception phase), so that prospective fathers and mothers only concentrate on preparing for pregnancy and childbirth. A healthy pregnancy requires physical and mental preparation from every mother. Planning a healthy pregnancy must be done before the pregnancy period. A well-planned pregnancy process will have a positive impact on the condition of the prospective mother and fetus. In connection with this, it is necessary to increase knowledge about premarital preparation as an effort to prevent stunting in a healthy pregnancy. The purpose of this service is to increase adolescent knowledge about premarital preparation as an effort to prevent stunting in healthy pregnancy, to increase adolescent knowledge about adolescent reproductive health education, to provide an overview of adolescents about premarital preparation as an effort to prevent stunting in healthy pregnancies